أقوال الإمام المباركفوري التفسيرية في كتابه الرحيق المختوم جمعا ودراسة: Imam Al-Mubarakfuri’s Interpretive Sayings in His Book Al-Rahiq Al-Makhtum: A Collection and Study - Adnan Moh’d Abdullah Shalash; Ragab Shehatah Mahmoud Moh’d (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
This study deals with the explanatory words of Imam Mubarakfuri in his book al-Rahiq al-Makhtum collection and study, and this research aims to collect the words of Mubarak's interpretation in his book Nectar Sealed and study by reference to the statements of interpreters, where the importance of the research is to add research from the interpretation of research in the books of the Prophet in this study. The researcher had followed the inductive and descriptive analytical approach, and the results of the study showed that Mubarak was able to support the historical events and the prophetic biography of the Holy Quran.